Phylogenetic analysis and preliminary classification of the Parathalassiinae (Diptera: Empidoidea: Dolichopodidae sensu lato) - Cumming, Jeffrey M.; Brooks, Scott E. (Zootaxa, 2019)
Phylogenetic relationships of the subgroups of Parathalassiinae are presented, based on a morphological cladistic analysis. Worldwide, all known extant genera, species groups and newly discovered undescribed lineages are represented in the analysis. Some previously proposed generic relationships are supported by the analysis, but recognition of many current genera renders the present concept of Microphorella Becker as both paraphyletic and polyphyletic. Microphorella merzi Gatt is here classified in Eothalassius Shamshev & Grootaert, as Eothalassius merzi (Gatt) comb. nov. A preliminary classification with all included extant lineages within the Parathalassiinae (at the genus and species group level) is outlined. The ranking of these lineages is discussed and several species groups of Microphorella may need to be elevated to generic or subgeneric level, whereas some currently recognized genera may need to be relegated to subgenera.